Bovine Serum Albumin-Conjugated Ferrimagnetic Iron Oxide Nanoparticles to Enhance the Biocompatibility and Magnetic Hyperthermia Performance - Kalidasan, Viveka; Liu, Xiao Li; Herng, Tun Seng; Yang, Yong; Ding, Jun (Nano-Micro Letters, 2015)
Magnetic hyperthermia is a fast emerging, non-invasive cancer treatment method which is used synergistically with the existing cancer therapeutics. We have attempted to address the current challenges in clinical magnetic hyperthermia-improved biocompatibility and enhanced heating characteristics, through a single combinatorial approach. Both superparamagnetic iron oxide nanoparticles (SPIONs) of size 10 nm and ferrimagnetic iron oxide nanoparticles (FIONs) of size 30 nm were synthesized by thermal decomposition method for comparison studies. Two different surface modifying agents, viz, Cetyl Trimethyl Ammonium Bromide and 3-Aminopropyltrimethoxysilane, were used to conjugate Bovine Serum Albumin (BSA) over the iron oxide nanoparticles via two different methods—surface charge adsorption and covalent amide bonding, respectively. The preliminary haemolysis and cell viability experiments show that BSA conjugation mitigates the haemolytic effect of the iron oxide nanoparticles on erythrocytes and is non-cytotoxic to the healthy Baby Hamster Kidney cells. It was observed from the results that due to better colloidal stability, the SAR value of the BSA-iron oxide nanoparticles is higher than the iron oxide nanoparticles without BSA, irrespective of the size of the iron oxide nanoparticles and method of conjugation. The BSA-FIONs seem to show improved biocompatibility, as the haemolytic index is less than 2 % and cell viability is up to 120 %, when normalized with the control. The SAR value of BSA-FIONs is 2300 W g−1 when compared to 1700 W g−1 of FIONs without BSA conjugation. Thus, we report here that BSA conjugation over FIONs (with a high saturation magnetization of 87 emu g−1) provide a single combinatorial approach to improve the biocompatibility and enhance the SAR value for magnetic hyperthermia, thus addressing both the current challenges of the same.